2021
DOI: 10.3390/land10070718
|View full text |Cite
|
Sign up to set email alerts
|

Making Rural Micro-Regeneration Strategies Based on Resident Perceptions and Preferences for Traditional Village Conservation and Development: The Case of Huangshan Village, China

Abstract: Micro-regeneration is a gradual renewal strategy that uses small-scale interventions to improve the quality of the living environment and local community, as well as spur industrial development. It is the small-scale interventions that have continued to make micro-regeneration a viable economic rural renewal approach for traditional village conservation and development. As such, in this work we explore potential micro-regeneration strategies and promotions based on assessments of public perception and preferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
0
0
Order By: Relevance
“…(Tousi et al, 2022) Focuses on urban acupuncture in Greek ex-refugee areas, highlighting its impact on urban morphology and microclimate. (Xi et al, 2021) Examines micro-regeneration strategies for rural renewal, emphasizing resident perceptions in traditional village conservation. (Ding et al, 2021) Delves into urban acupuncture for transforming old communities in historical districts, preserving heritage while improving public spaces.…”
Section: Review Of Literaturementioning
confidence: 99%
“…(Tousi et al, 2022) Focuses on urban acupuncture in Greek ex-refugee areas, highlighting its impact on urban morphology and microclimate. (Xi et al, 2021) Examines micro-regeneration strategies for rural renewal, emphasizing resident perceptions in traditional village conservation. (Ding et al, 2021) Delves into urban acupuncture for transforming old communities in historical districts, preserving heritage while improving public spaces.…”
Section: Review Of Literaturementioning
confidence: 99%
“…In order to avoid homogenized environmental design, when planning and designing outdoor activity spaces in villages, in addition to the urban-rural differences, the influence of villagers' personal attributes on spatial preferences should also be taken into account. Meanwhile, through the joint participation of designers and villagers, a better combination of "top-down" and "bottom-up" might be achieved [36].…”
Section: Influence Of Individual Attributes On Activity Space Preferencementioning
confidence: 99%
“…According to the survey, pre-retirement occupational attributes could affect the spatial preferences such as landscape styles, site noise, activity purposes, and activity status. It indicated that a person's previous occupation could affect their sense of aesthetics-those who have worked in an urban area were more likely to prefer urban-style landscapes and activities [36,41,42]. At the same time, villagers who were mental labors tended to prefer complex activity content, while those engaged in agricultural activities liked simpler activities more.…”
Section: Spatial Design That Reflected the Characteristics Of Differe...mentioning
confidence: 99%
“…For instance, certain scholars have employed questionnaire surveys to explore potential micro-revival tactics grounded in the assessment of rural residents' cognition and preferences. Their findings reveal that tourism is widely recognized and preferred as a method of industrial development [ 18 ]. Other scholars have delved into the impact of consumer behavior on economic development within the tourism sphere through field surveys, interviews, content analysis, and structural equation modeling [ 17 ].…”
Section: Introductionmentioning
confidence: 99%